KERANGKA KONSEPTUAL RANTAI PASOK MATERIAL KONSTRUKSI JALAN DI PULAU TIMOR - Djobul, Nadia Vanesa; Messah, Yunita A.; Bella, Rosmiyati A. (Fakultas Teknik, Universitas Wiraraja, 2025)
Good road construction is influenced by several resources, one of which is material. Road construction materials include aggregates and asphalt. These materials are held by service providers, namely material suppliers. Material suppliers are important in supporting road construction work in accordance with the time, cost, and quality that have been determined. These suppliers will form a network of cooperation called supply chains. A supply chain is a physical network consisting of companies that work together to provide raw materials, process them into finished goods, and deliver them to end users. Conceptually, the supply chain is built by several components, such as materials, suppliers, management, finance, transportation, weather, location, time, and the COVID-19 pandemic. This research was conducted to determine whether these components are important components in the smooth material supply chain. This research involved contractors working on road construction on Timor Island as resource persons. Data collection is done using the survey method, namely a closed questionnaire. Data processing and analysis techniques use descriptive statistical analysis with the help of SPSS software. Based on the results of the analysis, it shows that the success of road construction is built from component factors, namely materials, suppliers, management, finance, transportation, weather, location, and time. The COVID-19 pandemic is very important for the smooth supply chain of road construction materials on Timor Island.